Value Added Tax (Vat) Restitution Process For Construction Services At The Tax Consultant Office - Rustan Rustan; Ainun Mardiyah; Andi Arifwangsa Adiningrat (Jurnal Riset Perpajakan: Amnesty, 2023)
The value of tax value of the tax payment of tax payments by the Company's contact, the taxpayer not only has the right to pay taxes but also have the right to revisit tax payments that have been experiencing excess. The purpose of this study is to know and evaluate the value of the value of tax value (VAT) on construction services at the Tax Consultant Office in Makassar. This study was done at the Office of the Massaniga & Cost column for the sample using the customer data which is a taxpayer for construction activities. Techniques in this study using applied qualitative techniques. The research data obtained the author through field research both by observation and interview and supported by the acquisition of documents from the research place. The results showed that evaluation of the value-added tax restitution for the construction of existing Office of the Massaniga & PE-companion tax consultant, successfully effectively.